Preschool speech intelligibility and vocabulary skills predict long-term speech and language outcomes following cochlear implantation in early childhood. (July 2014) - Castellanos, Irina; Kronenberger, William G; Beer, Jessica; Henning, Shirley C; Colson, Bethany G; Pisoni, David B
<x content-type="archive" xml:space="preserve">Abstract</x> Speech and language measures during grade school predict adolescent speech-language outcomes in children who receive cochlear implants (CIs), but no research has examined whether speech and language functioning at even younger ages is predictive of long-term outcomes in this population. The purpose of this study was to examine whether early preschool measures of speech and language performance predict speech-language functioning in long-term users of CIs. Early measures of speech intelligibility and receptive vocabulary (obtained during preschool ages of 3–6 years) in a sample of 35 prelingually deaf, early-implanted children predicted speech perception, language, and verbal working memory skills up to 18 years later. Age of onset of deafness and age at implantation added additional variance to preschool speech intelligibility in predicting some long-term outcome scores, but the relationship between preschool speech-language skills and later speech-language outcomes was not significantly attenuated by the addition of these hearing history variables. These findings suggest that speech and language development during the preschool years is predictive of long-term speech and language functioning in early-implanted, prelingually deaf children. As a result, measures of speech-language functioning at preschool ages can be used to identify and adjust interventions for very young CI users who may be at long-term risk for suboptimal speech and language outcomes.